Human Rights and Constitutional Sovereignty in The Context of The Struggle for Legal Justice - Diharjo, Nugroho Noto; Muhtar, Mohamad Hidayat; Rahim, Erman I; Rachman, Sri Nurnaningsih; Saija, Vica Jillyan Edsti; Lubis, Arief Fahmi (Bacarita Law Journal, 2024)
The universal protection of human rights rests on a set of basic concepts known as human rights. This research aims to analyze (1) How does the low level of constitutional awareness among Indonesian society affect the implementation of human rights (HAM) and constitutional sovereignty in real practice? and (2) What is the impact of the lack of citizenship education on understanding constitutional rights and responsibilities as citizens towards realizing the goals of social justice mandated by the Indonesian constitution?. The research method used in this research is normative legal research with a descriptive analytical approach. The research results show that low constitutional awareness has a serious impact on the implementation of Human Rights and the sovereignty of a country's constitution. Citizenship education is likened to a rail or means that guides citizens to become good citizens. Increasing constitutional awareness and citizenship education are expected to support the struggle for legal justice in Indonesia. It is hoped that a society that is more aware of the constitution can play an active role in protecting and fighting for human rights (HAM), as well as supporting constitutional sovereignty to achieve the goals of social justice.